Concrete pipes and ancillary concrete. Unreinforced and reinforced concrete pipes (including jacking pipes) and fittings with flexible joints (complementary to BS EN 1916:2002). Specification Part 1, (13th August 2021) - British Standards Institution,
No abstract available